PENGEMBANGAN MOBILE-LEARNING (M-LEARNING) BERBASIS ANDROID MENGGUNAKAN PLAYER OPEN SWF 2.0.7 PADA MATERI PENGENALAN MEDIA TRANSMISI1 - Wijayanto .; Arif Wibisono; Ika Menarianti (Universitas PGRI Semarang, 2015)
This study aimed to obtain a valid media Mobile Learning for self-learning students in material introduction transmission media. In this study using respondents the third semester students as much as 2 classes Study Program University of Information Technology Education PGRI Semarang. Development of Mobile Learning media is done with 4 stages adapted from Akker (1999), which includes 1) Analysis Introduction, 2) Design, 3) evaluation, 4) Revision. Processing the data using descriptive qualitative data analysis techniques. Appropriate statistical analysis of test results on the t-test for Equality of Means obtained sig (2-tailed) in value after was <0.05. It can be concluded that the value of mobile learning conditions applied after better than before deploying mobile learning. Gained an average of learning outcomes (Mean) is better between the experimental class of 83.44 compared with 79.33 for the control class. From the results obtained instructional media android based Mobile-Learning valid for self-learning students in material introduction transmission medium. ?é?á Keywords : Mobile-Learning, Material of Transmission Media, Android